Clinical and laboratory profile of Kyasanur forest disease in a tertiary care hospital in Goa - Nayak, Chitralekha; Viegas, Ruth; Gomes, Edwin (International Journal of Research in Medical Sciences, 2026)
Background: Kyasanur Forest Disease (KFD), a tick-borne viral hemorrhagic fever once confined to the Western Ghats of Karnataka, India, has spread to adjacent states, including Goa, in recent years. This study aimed to analyze the clinical profiles of confirmed adult KFD cases at a tertiary care hospital. Methods: A retrospective observational study was conducted in the Department of Medicine, Goa Medical College, from June 2016 to June 2017. Case records of all RT-PCR-confirmed adult KFD cases were reviewed for demographic, clinical and laboratory data and analyzed using descriptive statistics. Results: Fifty-seven confirmed adult cases were analyzed (mean age 41.65 years; 63.16% female). The majority of cases arose from Sawantwadi and Dodamarg talukas of Sindhudurg District, Maharashtra, with a seasonal peak in March-April. Fever was universal, followed by myalgia (52.6%), vomiting (52.6%), and diarrhea (50.8%). Lower respiratory tract involvement occurred in 35.1% and pneumonia in 8.8%. Neurological complications were observed in 17.5% of patients, including meningoencephalitis, cerebellitis, and quadriparesis. Hemorrhagic manifestations occurred in 17.5%. Leucopenia was present in 94.7%, with marked leucopenia (<2000 cells/mm3) in 52.6%. Thrombocytopenia was noted in 70.2% and elevated transaminases in 91.2%. Renal involvement was rare (1.75%). One patient died due to pneumonia. Conclusions: KFD presents with diverse early manifestations, predominantly gastrointestinal, respiratory, hemorrhagic involvement with neurological impairment in some cases associated with marked leucopenia and elevated liver enzymes which may mislead clinicians. Further detailed clinical and epidemiological aspects of KFD need to be explored for better understanding of the disease.